A theoretical study of the ligand-controlled palladium-catalysed regiodivergent synthesis of dibenzosilepin derivatives. Issue 3 (23rd December 2022) - Yan, Xueyuan; Yang, Miao; She, Yuan-Bin; Yang, Yun-Fang
Abstract : The mechanism and origin of the regioselectivity of ligand-controlled palladium-catalysed reigodivergent synthesis of silicon-bridged π-conjugated compounds were elucidated with density functional theory calculations. Abstract : Palladium-catalysed ligand-controlled 1, n -palladium migration of silicon-tethering substrates provides a regiodivergent synthesis strategy for constructing silicon-bridged π-conjugated compounds possessing a 6, 6-fused or a 5, 7-fused scaffold. Density functional theory (DFT) calculations were carried out to elucidate the detailed mechanism of this 1, n -palladium migration involving syn - or anti -carbopalladation. The computational results suggest that alkyne insertion is the regioselectivity-determining step. Upon catalysis without the BINAP ligand, the 1, 2-insertion of an alkyne into the Pd–aryl bond leads to the formation of 6, 6-fused benzophenanthrosiline, which is more favorable than the 2, 1-insertion of alkyne by 4.2 kcal mol −1 . The selective formation of 5, 7-fused benzofluorenosilepins via the 2, 1-alkyne insertion is facilitated by the BINAP ligand. The 1, 2-alkyne insertion with the BINAP ligand is disfavoured due to the steric repulsion between the phenyl group of the substrate and the naphthalene group of the BINAP ligand. The 2, 1-alkyne insertion with the BINAP ligand orients the ligand away from the phenyl group of the substrate, which can avoid steric repulsion.